Artistic and Reflective Analysis of “Nadeed” - Hassan, Amer (sourcecoder, 2023)
"Nadeed" is a symbolic novel. The story revolves around the residents of a blind house. Baba is the main character and Bhola, Sharfu, Rooni, Singha, Lakhi foot main and Mahaguru. The Baba loses his eyesight in an accident during his childhood and after an accident, he regains his sight in an accident during old age. But he keeps pretending to be blind for the world. A foreign agency hires him and he gets involves in Hindu - Muslim riots. His conscious awakes in the end and he save the blind and foreign minister from death. He dies after writing a letter about his leader, foreign agents and all that he has been doing.